A new anthophilic species of Drosophila Fallén belonging to the bromeliae group of species (Diptera, Drosophilidae). - (:unkn) unknown (Sociedade Brasileira de Zoologia, 2004)
Drosophila speciosa sp. nov. from: Belém, Pará, Brazil, is described and morphologically compared to a closely related species, D. aguape Val & Marques, 1996. Adult specimens of D. speciosa sp. nov. were collected while visiting T. speciosum Willd. ex Spreng. flowers in EMBRAPA's Theobroma Linnaeus germoplasm collections (113 individuals) in Belém and in Caxiuanã Scientific Station, in Melgaço, Pará, Brazil (four individuals). Emergent were obtained from T. speciosum flowers in both localities being four adults in Caxiuanã and 532 in EMBRAPA. Other eight emergencies were registered from Passiflora edulis Sims flowers in Curuçá, Pará, Brazil.
Keywords: Drosofilídeos; Moscas antofílicas; Polinização; Theobroma speciosum; Anthophilic flies; Drosophilids; Pollination